2011
DOI: 10.1111/j.1555-2934.2011.01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Children, Preserving Families: Moral Conflict and Actuarial Science in a Problem of Contemporary Governance

Abstract: The United States Child Protective Services system is shaped by the unresolved tension between the aims of child protection and family preservation. Since the 1980s, child welfare experts have recommended the use of risk assessment tools in the hopes of standardizing the decisions made by social workers and judges. In this article, I show that despite their bureaucratic appearance, the tools implemented lacked a clear directive, allowing unresolved value conflicts to be papered over by the appearance of techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
(16 reference statements)
0
16
0
1
Order By: Relevance
“…The ideal types of bureaucratic organization that Weber described set up paradoxes that later organizational theorists would seize upon as an extremely productive strawman (Hoag 2014): the more rules are enforced, the less they are followed (Gouldner 1954); rules set out to achieve goals become goals in themselves, and ultimately subvert those original goals (Merton 1936(Merton , 1968 or are executed by people with no knowledge of the context (Crozier 1964); "informal" bureaucratic norms turn out to be critical to achieving formal goals (Barnard 1938;Blau 1955;Selznick 1966), and so on. 3 Later generations of authors writing in anthropology showed how attempts to homogenize the practice of bureaucratic policy create more opportunities for heterogeneous interpretation (Sandvik 2011); how rules seem never specific enough to guide practice clearly for a local context (Scherz 2011); and how people known for their warmth and hospitality become cold automatons (Herzfeld 1992). These paradoxes convey the paradoxical place that bureaucracy occupies within Western discourse more broadly: orderly and important, and yet horrifically, comically absurd, a position perhaps captured most evocatively by Franz Kafka (1946Kafka ( , 1993Kafka ( , 1998.…”
Section: Bureaucratic Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal types of bureaucratic organization that Weber described set up paradoxes that later organizational theorists would seize upon as an extremely productive strawman (Hoag 2014): the more rules are enforced, the less they are followed (Gouldner 1954); rules set out to achieve goals become goals in themselves, and ultimately subvert those original goals (Merton 1936(Merton , 1968 or are executed by people with no knowledge of the context (Crozier 1964); "informal" bureaucratic norms turn out to be critical to achieving formal goals (Barnard 1938;Blau 1955;Selznick 1966), and so on. 3 Later generations of authors writing in anthropology showed how attempts to homogenize the practice of bureaucratic policy create more opportunities for heterogeneous interpretation (Sandvik 2011); how rules seem never specific enough to guide practice clearly for a local context (Scherz 2011); and how people known for their warmth and hospitality become cold automatons (Herzfeld 1992). These paradoxes convey the paradoxical place that bureaucracy occupies within Western discourse more broadly: orderly and important, and yet horrifically, comically absurd, a position perhaps captured most evocatively by Franz Kafka (1946Kafka ( , 1993Kafka ( , 1998.…”
Section: Bureaucratic Organizationsmentioning
confidence: 99%
“…One might see Kafka's work in such a light, but also that of Bowker and Star (2005) (1977) famous analysis of former Nazi officers on trial at the Nuremberg Trials, which explained that bureaucracy generates "rule by nobody" through the physical and cognitive separation of decisionmakers from those they decide upon. Others, writing often from a Foucauldian perspective, show how the discourses and bureaucratic practices of development (Ferguson 1990), refugee assistance (Sandvik 2011), child protection services (Scherz 2011), child welfare and poverty alleviation (Gupta 2012), and others convert political questions into technical ones. In these cases, authors have tended to find that bureaucracies ultimately reinforce the existing political order, even though bureaucrats and clients might assert themselves at some level (see also Telesca 2015), a tacit-if only partial-affirmation of Weber's "iron cage."…”
Section: Bureaucratic Organizationsmentioning
confidence: 99%
“…In a range of anthropological accounts, people's encounters with street‐level bureaucrats—those who work on the front lines of state, corporate, or development institutions—have been characterized as threats to dignity. In some cases, overworked street‐level bureaucrats can feel pressed to “psychologically simplify” and “mass process” their clientele, discounting individual stories of pain and suffering (Herzfeld ; Lipsky , xii; Scherz ; Ticktin ). In other cases, bureaucrats resolve the problems of overwork and under‐resourcing through extortion or discrimination (Gupta ; Hoag ).…”
Section: Orientation Dignity and Craftmentioning
confidence: 99%
“…In doing so, I build on an emerging focus on the child welfare system in anthropological scholarship. Research in this area has focused on decision‐making processes in the child welfare system (Scherz ); the interplay of competing actors in child protection cases (Reich ); the role of child welfare systems in policing families of undocumented migrants (Briggs ); the contradictions in which interventions of child welfare can exacerbate the inequalities experienced by working‐class parents in particular (Lee ); the ways in which these systems impact localized communities (Roberts ); and the oft‐racialized logics that make particular groups, such as African Americans, more vulnerable to intervention (Roberts ). Those studies pertain to North American contexts, but despite similar tensions attached to systems of child welfare in Australia, there is little comparable ethnographic research, especially in terms of how child protection interventions particularly effect minority communities.…”
mentioning
confidence: 99%
“…As other scholars have recognized (Reich ; Rose ), it can, at times, be that; but the stakes of protecting children from the potential of harm and death is, nonetheless, very real. By being held accountable in both institutional frameworks and public discourse for the welfare of children, there is tremendous pressure on workers who implement child removal interventions to predict possible futures in order to determine what is in the “best interests” of a child (Rodriguez ; Scherz ). Still, it is important to recognize that social welfare institutions are not neutral (Roberts ); neither are the decisions of the workers who implement them—regardless of their objective to “protect.”…”
mentioning
confidence: 99%